Hemoglobin A1c Relates to Poorer Scores on a Test of Executive Function. (7th June 2021) - Smith, Aaron; Song, Xing; Taylor, Matthew; Sullivan, Debra
Abstract: Objectives: Poor glycemic control (GC) is associated with poorer executive function. However, data looking at the relationship between GC and cognition is limited. This study aimed to assess the relationship between GC and various cognitive tests using electronic medical record data (EMR). Hemoglobin A1c (HbA1c) was the main predictor variable. Methods: De-identified data were gathered from an midwestern academic medical center's EMR in an i2b2 based clinical data repository. Participants were seen at the hospital's memory clinic with a HbA1c lab value (CPT Code: 83, 036) on record. 566 participants were used in the final analysis. The most recent cognitive score from the following cognitive tests were used as the response variables, Trail Marking Part A and B and Verbal Fluency. The median value was derived from each participant's three most recent HbA1c values. We constructed ordinary least squares regression models to assess HbA1c's relationship with individual cognitive tests. The model included race, Mild Cognitive Impairment, Alzheimer's Disease, income, and age as covariates. Statistical analyses were performed using R (v. 3.6.2; R Foundation, Vienna, Austria). Statistical significance was set at p < 0.05. Results: Participants were 54% male and had a mean age of 75 ± 9.2 years. Mean HbA1c value was 6.14 ± 1.2. Higher HbA1c values were related to poorer performance on the Trail Making Part A test (β = –0.02, p < 0.01). HbA1c was not related to other individual cognitive tests: Trail Making Part B (β = –0.019, P  = 0.70), Verbal Fluency (β = 0.30, P  = 0.13). Conclusions: There was a strong relationship between HbA1c and performance on the Trail Making Part A test, a sensitive test for executive function. This study adds to the literature that poor GC worsens executive function. Consequently, maintaining GC with healthy lifestyle choices may be important for healthy aging. There was no significant relationship between HbA1c and other cognitive tests. Future analyses with more robust statistical modeling will be more informative for understanding the relationship between HbA1c and cognitive tests. Funding Sources: Clinical and Translational Science Awards.